Macroscopic and Microscopic Mechanisms of Cement-Stabilized Soft Clay Mixed with Seawater by Adding Ultrafine Silica Fume - Qiang Li; Jie Chen; Qian Shi; Shihao Zhao (Advances in Materials Science and Engineering)
The strength of the cement-stabilized soil can be improved by the use of seawater. Compressive strength test results show that the strength of cement-stabilized soil mixed with seawater is 50% greater than that mixed with freshwater at the 90th day. However, the application is limited because the expansion of the cement-stabilized soil mixed with seawater increases significantly. A kind of ultrafine silica fume was added into the cement-stabilized soil to inhibit swelling of the cement-stabilized soil with seawater. The expansion of cement-stabilized soil mixed with seawater by adding ultrafine silica fume is close to that of cement-stabilized soil mixed with freshwater. With the addition of ultrafine silica fume, the unconfined compressive strength increases by close to 6.5% compared with seawater alone at the 90th day. The mechanisms of adding ultrafine silica fume into the cement-stabilized soil mixed with seawater are revealed by several physical and chemical characterization parameters, such as specific gravity, unbound water content, surface morphology seen with SEM, and crystal products by X-ray diffraction tests. The results show that the crystal growth is an important factor, affecting the strength and expansion of cement-stabilized soil mixed with seawater.